VISA MASUK KOTA: ALTERNATIF KEBIJAKAN KAUM URBAN UNTUK MENGATASI KEPADATAN PENDUDUK JAKARTA - Abraham, Razii; Lubis, Dicky Iqbal; Indrawan, Muhamad; Fachrudin, Ridwan (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Jakarta is area with the highest population density in Indonesia, and acts as a Center for Economic Capital and the State. One factor is the density of population is high urbanization. We put forward the city a model of entry visas as a form of legalization for the urban policies aimed at regulating migration and controlling the number of entrance. Furthermore, the necessary parties supporters to be able to carry out the implementation of the strategic entry visa this city include the establishment of a special body to handle visas entered the city. Eventually we hope to visa entry system the city is able to take control of the number of migrants coming to Jakarta.